2009
DOI: 10.1152/ajpheart.01317.2008
|View full text |Cite
|
Sign up to set email alerts
|

The effects of propofol on vascular function in mesenteric arteries of the aging rat

Abstract: Gragasin FS, Davidge ST. The effects of propofol on vascular function in mesenteric arteries of the aging rat. Hypotension following administration of propofol, an anesthetic agent, is strongly predicted by advanced age and is partly due to direct vasodilation. We hypothesized that propofol increases nitric oxide (NO)-mediated vasodilation by enhancing its bioavailability in the aged adult vasculature, leading to greater vasodilation than in the young adult. Small mesenteric arteries from rats aged 13-15 versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…[3][4][5] Prior studies have also demonstrated that 2,6 diisopropyl phenol (propofol) can modulate CBF by decreasing the metabolic rate of oxygen; in addition, speculation based on animal studies suggests that propofol can dilate vascular smooth muscle in other regions of the body. 6 The basis of this study is that the authors had noted prominent LMCE on brain MR imaging in some sedated children, but based on clinical notes, they neither were acutely ill nor exhibited meningeal signs. Thus, this study was initiated to determine whether the degree of this phenomenon of apparent LMCE (termed here "pseudo"-LMCE) relates to the type of T1WI sequence, time to acquiring postcontrast T1WI, propofol dosage, or various patient demographics.…”
mentioning
confidence: 95%
“…[3][4][5] Prior studies have also demonstrated that 2,6 diisopropyl phenol (propofol) can modulate CBF by decreasing the metabolic rate of oxygen; in addition, speculation based on animal studies suggests that propofol can dilate vascular smooth muscle in other regions of the body. 6 The basis of this study is that the authors had noted prominent LMCE on brain MR imaging in some sedated children, but based on clinical notes, they neither were acutely ill nor exhibited meningeal signs. Thus, this study was initiated to determine whether the degree of this phenomenon of apparent LMCE (termed here "pseudo"-LMCE) relates to the type of T1WI sequence, time to acquiring postcontrast T1WI, propofol dosage, or various patient demographics.…”
mentioning
confidence: 95%
“…In our studies, we demonstrated that propofol causes enhanced mesenteric artery relaxation in aged rats when compared to young, and this effect was attributed to increased NO bioavailability (Gragasin and Davidge, 2009). We also demonstrated that the combination of antioxidant enzymes superoxide dismutase and catalase enhance vasodilation to acetylcholine similar to propofol in aged rats (Gragasin and Davidge, 2009).…”
Section: Vascular Changes Associated With Aging and Effects Of Anesthmentioning
confidence: 82%
“…We also demonstrated that the combination of antioxidant enzymes superoxide dismutase and catalase enhance vasodilation to acetylcholine similar to propofol in aged rats (Gragasin and Davidge, 2009). On the basis of these studies, we suggested that propofol may exert part of its vasodilatory effects via intrinsic antioxidant effects (Ansley et al, 1998), since it is structurally similar to α-tocopherol (vitamin E).…”
Section: Vascular Changes Associated With Aging and Effects Of Anesthmentioning
confidence: 90%
“…However, there is a marked variability in cardiovascular sensitivity to propofol among patients. This variability may induce the serious side effect of hypotension, especially in elderly and hypertensive patients [5] . There are several mechanisms that are known to cause the hypotensive effects …”
Section: Discussionmentioning
confidence: 99%
“…However, propofol has the potential side effect of hypotension, which especially affects elderly patients [3] and hypertensive rats [4,5] . The wide variability of sensitivity to propofol may lead to circulatory instability among patients, the underlying mechanisms of which are complicated.…”
Section: Introductionmentioning
confidence: 99%